Collagen synthase P4HA3 as a novel biomarker for colorectal cancer correlates with prognosis and immune infiltration - Xiaohuan Guo; Yu Zhang; Lina Peng; Yaling Wang; Cheng-Wen He; Kaixuan Li; Ke Hao; Kaiqiang Li; Zhen Wang; Haishan Huang; Xiaolin Miao (Heliyon, 2024)
Objective: In this study, we aimed to determine whether proly4-hydroxylase-III (P4HA3) could be used as a biomarker for the diagnosis of colorectal cancer (CRC) as well as for determining prognosis. Methods: We used The Cancer Genome Atlas (TCGA) database to analyze P4HA3 expression in CRC and further investigated the association between P4HA3 and clinicopathological parameters, immune infiltration, and prognosis of patients with CRC. Enrichment analysis was conducted to investigate the potential biological role of P4HA3 in CRC. To verify the results of TCGA analysis, we performed immunohistochemical staining of 180 clinical CRC tissue samples to probe into the relationship of P4HA3 expression with lymphocyte infiltration and immune checkpoints expression. Results: The expression of P4HA3 was significantly higher in CRC tissues and associated with a higher degree of malignancy and poorer prognosis in CRC. The results of enrichment analysis indicated that P4HA3 may be associated with the epithelial-mesenchymal transition process and the immune response. Immunohistochemical staining results showed that high P4HA3 expression was associated with high infiltration levels of CD8+ and Foxp3+ TILs and high PD-1/PD- L1 expression. Lastly, patients with CRC co-expressing P4HA3 and PD-1 had a significantly worse prognosis. Conclusion: High expression of P4HA3 is associated with adverse clinical features and immune cell infiltration in CRC, and has the potential to serve as a biomarker for predicting CRC prognosis.